2013
DOI: 10.1007/s00264-013-1832-6
|View full text |Cite
|
Sign up to set email alerts
|

Complications with reverse total shoulder arthroplasty and recent evolutions

Abstract: Since its description by Paul Grammont from Dijon, France, several tens of thousands of reverse total shoulder arthroplasties (RTSA) have been performed for diverse conditions. The purpose of this analysis is to identify the complications of this procedure in the literature and in clinical practice. A total of 240 papers concerning RTSA published between 1996 and 2012 have been identified. Over 80 papers describe complications associated with this type of implant. A list of prostheses satisfying European and U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
80
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(81 citation statements)
references
References 50 publications
0
80
1
Order By: Relevance
“…The incidence of SN was variable, ranging from 0 to 96 %, and increased with longer follow-up [8,11,12]. In this study, we found SN in 30 % of our patients.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…The incidence of SN was variable, ranging from 0 to 96 %, and increased with longer follow-up [8,11,12]. In this study, we found SN in 30 % of our patients.…”
Section: Discussionmentioning
confidence: 48%
“…The failure to achieve appropriate deltoid tension in these cases is a well-known cause of instability [11,15]. Although good results after RSA are well documented, the problem of SN is of concern.…”
Section: Discussionmentioning
confidence: 99%
“…The use of semi-constrained reverse shoulder arthroplasty could theoretically reduce the rate of recurrent dislocation due to the inherent stability of this implant design [16]. Moreover, in cases of insufficient rotator cuff, favourable results have been described compared to non-constrained anatomic shoulder arthroplasty [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…In the last two decades, the number of shoulder arthroplasties has increased every year, probably due to the advances in implant design and surgical technique, which have made complicated surgical procedures possible [1,2]. However, many complications may affect the mid-and long-term results of this type of surgery, leading to loss of function, pain and failure of the implant.…”
Section: Introductionmentioning
confidence: 99%